Soluble RAGEs – Prospects for Treating & Tracking Metabolic and Inflammatory Disease - Schmidt, Ann Marie (Vascul Pharmacol, 2015)
Emerging evidence links the receptor for advanced glycation endproducts (RAGE) to the pathogenesis of tissue damage in chronic metabolic and inflammatory diseases. In human subjects, multiple reports suggest that in the plasma/serum, circulating levels of distinct forms of soluble RAGEs may be biomarkers of the presence or absence, and the extent of chronic disease. These considerations prompt us to consider in this review, what are soluble RAGEs; how are they formed; what might be their natural functions; and may they serve as biomarkers of inflammatory and metabolic disease activity? In this brief review, we seek to address what is known and suggest new areas for scientific investigation to uncover the biology of soluble RAGEs.